Față în față cu moartea. Eroul și călătoria în lumea de dincolo (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Florina-Cosmina Podaru explores the heroic confrontation with death in ancient literature, focusing on Gilgamesh, Odysseus, and Aeneas. The study analyzes Gilgamesh’s transition from seeking glory to experiencing profound fear after Enkidu’s death. By examining the journey to the underworld, the author highlights how heroes transcend mortality to gain self-knowledge and validate cultural beliefs. Ultimately, the heroic descent into the afterlife reflects universal human anxieties and the perpetual quest for identity and immortality. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.